Penggunaan Chanel Youtube Sebagai Media Pembelajaran Mata Pelajaran Sejarah Pada Siswa Kelas VII SMPN 1 Kalidawir Tulungagung - Dendy Nurkhosim; Dita Hendriani (Jurnal Ilmu Pendidikan dan Sosial, 2023)
The digital era has entered the era of the industrial revolution 4.0, the work process and way of life of humans have also changed following these changes. The development of the industrial revolution made all processes systematic and automatic, not only there the development of internet technology is also increasingly advanced making all information easy to find. With the birth of the internet, YouTube was created as an attractive medium for spreading information. This can be utilized in the world of education as a learning medium that attracts students' interest. Departing from this phenomenon, in this study the researcher was interested in conducting research related to the use of YouTube media as a means of learning historical heritage material with a Hindu-Buddhist pattern in class VII SMPN 1 Kalidawir. This research was conducted using qualitative methods with descriptive research types. Primary data sources on teachers and students of class VII. Secondary data sources; research journals, books and youtube media. Data collection techniques include; interview techniques, observation and documentation in the field. After the desired data is collected and analyzed. The results of the study state that the use of YouTube as a learning tool is able to attract students' interest in learning while in class and facilitate students and teachers in learning so that the learning and teaching process can run effectively and efficiently.